PENGARUH METODE BERCERITA KISAH NABI TERHADAP PERKEMBANGAN KARAKTER PADA ANAK USIA DINI DI TK AL-MAARIF KALISAT- JEMBER - Fitriatiningsih; Ianatuz Zahro; Trio Suwargono (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study used a sample of 25 children with character traits aged 6-7 years in class B using Purposive sampling techniques. This study is a Pre-Experimental study. Data analysis in this study uses descriptive statistical analysis, Prerequisite Tests (Normality Test and Homogeneity Test) and Hypothesis testing. Descriptive Tests are used to describe the characteristics of the data. While the Prerequisite Test is used to determine whether the data is normally distributed or not and to determine whether 2 groups have the same characteristics. Hypothesis testing is used to see the effect of the method of telling the story of the Prophet on the development of characteristics in early childhood. The results of this study are 2, namely H0 if there is no effect and H1 if there is an effect of the method of telling the story of the Prophet on the development of character values in early childhood. The output of this study is expected to contribute to PAUD teachers as an alternative method of character learning that is interesting, contextual, and appropriate to the stages of child development. In addition, the results of this study can be used as reference material in the preparation of learning programs based on Islamic values in early childhood education environments.